The Right to Strike in Romania: Between Freedom of Expression and Democracy - Nenu, Carmen-Constantina (PRAWO i WIĘŹ, 2026)
This study aims at analysing the right of judges to make strike, requests and comments on their status, including the social policy regarding service pensions. The analysis takes into account the freedom of expression of judges in the relationship with the Government and the Parliament in matters of interest for the justice system and their obligation to show restraint in their behaviour in order to avoid compromising their independence and impartiality.